DEATH Historiography In Islam dan French historical tradition: Study on Wafiyāt al-A’yān wa Abnāu Abnāi Zamān and Western Attitude Toward death from The Middle Age to The Present - Tolib Rohmatillah (Tsaqofah dan Tarikh: Jurnal Kebudayaan dan Sejarah Islam, 2022)
Historiography of death between Arab-Islam and French tradition has different root and models. As Arabian model wafiyat came into being as new systematic mode of writing bibliographical dictionary, it is French la histoire la morte was the French innovation in social history by Annales school. To make clear comparison, two book are selected that are Wafiyāt al-A’yān wa Abnāu Abnāi Zamān by Ibn Khalikan and Attitude tward Death by Philip Aries. To study these two books, comparative historiography is applied to make a comparison and contrast between genre, style and sources. As the result of taking study of comparison, so there are similarity and differences between two historical tradition in the from of content and method of writing history. These two types are similar in one common trait constructed the idea based on death. However, it is clearly different in as much as that Arabic wafiyat is prosopography and has relgious content and intend; meanwhile French death historiography is social history and growth in the idea of study of mentalites.